Combinatorial algorithms making support of managerial decisions - Donets, G.A.; Pepelyaev, V.A.; Trofymchuk, O.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The bounded and unbounded combinatorial recognition problems are posed. Using a problem of switches as an example, we show how to divide the subset of switches into groups so that the given number of faulty switches could be found by minimal number of tests. We also consider the problem of choosing the number of elements of the same type from two given sets. For every problem, we give the evaluating formulas for the minimal number of tests.